„Prepovedane teme” v sodobni umetnostni vzgoji? - Zupančič, Tomaž (Revija za elementarno izobraževanje, 2011)
“Forbidden topics” in Contemporary Visual Arts Education. The article presents a study on whether all works of modern art are appropriate for use in visual arts education in schools. The study focuses on artwork that addresses violence, killing and self-mutilation. The article presents contemporary art education theories on the given topic. It includes a description of chosen artwork, methodology and results of a study that was conducted on a sample of art pedagogy students. The findings did not reveal any change in what is already known about this topic, as we predicted. But it did provide some general directions on how to deal with this subject matter in the future.
Keywords: contemporary visual art; art education; violence; postmodernism; visual art didactics